2008
DOI: 10.1007/bf03191367
|View full text |Cite
|
Sign up to set email alerts
|

ACM sets of points in multiprojective space

Abstract: If X is a finite set of points in a multiprojective space P n 1 ×· · ·×P nr with r ≥ 2, then X may or may not be arithmetically Cohen-Macaulay (ACM). For sets of points in P 1 × P 1 there are several classifications of the ACM sets of points. In this paper we investigate the natural generalizations of these classifications to an arbitrary multiprojective space. We show that each classification for ACM points in P 1 × P 1 fails to extend to the general case. We also give some new necessary and sufficient condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…For any finite set of points X ⊆ P n 1 × · · · × P nr , it can be shown (see, for example [12, Theorem 2.1]) that dim R/I X = r and 1 ≤ depth R/I X ≤ r. When depth R/I X = r, then we say X is arithmetically Cohen-Macaulay (ACM). Although it remains an open problem to classify ACM sets of points in a multiprojective space (see [12] for some work on this problem), it can be shown that the separators of ACM sets of points have a particularly nice property:…”
Section: Separators Hilbert Functions and Acmnessmentioning
confidence: 99%
See 4 more Smart Citations
“…For any finite set of points X ⊆ P n 1 × · · · × P nr , it can be shown (see, for example [12, Theorem 2.1]) that dim R/I X = r and 1 ≤ depth R/I X ≤ r. When depth R/I X = r, then we say X is arithmetically Cohen-Macaulay (ACM). Although it remains an open problem to classify ACM sets of points in a multiprojective space (see [12] for some work on this problem), it can be shown that the separators of ACM sets of points have a particularly nice property:…”
Section: Separators Hilbert Functions and Acmnessmentioning
confidence: 99%
“…Although the converse of Theorem 2.6 fails to hold in general (see [12,Example 5.10]), the converse holds in P 1 × P 1 as first demonstrated by Marino:…”
Section: Separators Hilbert Functions and Acmnessmentioning
confidence: 99%
See 3 more Smart Citations